Large‐Scale Fabrication of Three‐Dimensional Surface Patterns Using Template‐Defined Electrochemical Deposition. (13th September 2012) - Yang, Shikuan; Lapsley, Michael Ian; Cao, Bingqiang; Zhao, Chenglong; Zhao, Yanhui; Hao, Qingzhen; Kiraly, Brian; Scott, Jason; Li, Weizhou; Wang, Lin; Lei, Yong; Huang, Tony Jun
Abstract A new strategy to achieve large‐scale, three‐dimensional (3D) micro‐ and nanostructured surface patterns through selective electrochemical growth on monolayer colloidal crystal (MCC) templates is reported. This method can effectively create large‐area (>1 cm2), 3D surface patterns with well‐defined structures in a cost‐effective and time‐saving manner (<30 min). A variety of 3D surface patterns, including semishells, Janus particles, microcups, and mushroom‐like clusters, is generated. Most importantly, our method can be used to prepare surface patterns with prescribed compositions, such as metals, metal oxides, organic materials, or composites (e.g., metal/metal oxide, metal/polymer). The 3D surface patterns produced by our method can be valuable in a wide range of applications, such as biosensing, data storage, and plasmonics. In a proof‐of‐concept study, we investigated, both experimentally and theoretically, the surface‐enhanced Raman scattering (SERS) performance of the fabricated silver 3D semishell arrays.